Technology transfer : a case study analysis of the Saudi oil and petrochemical sectors - Al Ankari, Abdulrahman (Cranfield University, 2009)
In the recent past a number of technologies have been imported into The Kingdom of Saudi Arabia. This experience has affirmed the conviction that technology can make an invaluable contribution to the growth of The Kingdom of Saudi Arabia. However, in doing so, the Kingdom of Saudi Arabia, like other nations, faces some questions of possible obstacles, trials and errors during the course of industrial development and technology transfer, that can be addressed by utilising science and technology efficiently to develop many sectors, improve output of industry, develop standards and -status of national manpower and its utilisation. This study analyses issues related to successful technology transfer in Saudi industry As such, the purpose of this study is to examine the relationship between industrial development and technology transfer in the Kingdom of Saudi Arabia, and the important role that modem technology can play in development of the oil and petrochemicals sectors. The aims are to provide a better understanding of the linkage between technology transfer and industrial development strategies in general, with special emphasis on the performance of the Saudi oil and petrochemical industry in particular. As such, to avoid failures on technology transfer, it becomes an imperative to analyse technology transfer by considering various approaches, as follows: Technology and industry is a key to future growth in Saudi Arabia - The main objective here is to locate, attract and keep industry. The concept of technology and industry deals with role of technology and the dynamics of Saudi's industry environment to excel in markets. Strategy at the functional level - this relates to the various activities assigned to different departments in the organisational structure. The concept means that all functions must be conducted in accordance with industry, technology and strategy. Strategy and technology - this means how to transfer an already existing technology to Saudi industry. Strategy for research and development - The concept deals mainly with how to plan, finance and implement R&D for products, security, environmental protection etc. Where to draw the line between general and specific objectives in R&D. The chosen method to study these issues is case study analysis of SABIC (Saudi Basic Industries Corporation) and Saudi Aramco (Saudi Arabian Oil Company). SABIC has been established for two main strategic objectives that go together in two parallel lines. The first objective aims to develop human resources and to turn them into a trained category that has the capability to transfer, assimilate and develop the most sophisticated technologies. The second objective aims to develop the natural resources and convert them to industrial products, helping to diversify the domestic income sources and open iii the doors for building up processing industries to satisfy the local and external market requirements. The first case study (SABIC) provides an overview of the phenomenon of technology transfer to the Kingdom of Saudi Arabia. For comparative purposes the second case study involves a case study of Saudi Arabia's largest oil firm (Saudi Aramco). These two case studies have been selected for their: i role in technology transfer in Saudi oil and petrochemical sectors, ii approach and access to greater resources in technology transfer, iii exposure of firm behaviour in the Saudi industrial sector, iv contribution to Saudi economic development and realisation of additional income through improved operations. The two case studies, typical of large companies not only in Saudi Arabia but also in the world, will address the obstacles in learning, committing and increasing performance through technology transfer. These cases highlight a range of choices available in technology transfer, which provide a wide range of means for technological learning through transfer. They offer different opportunities for further innovation and technology development. Although Saudi Aramco and SABIC claim 80 percent and 73 percent " Saudisation", respectively, the survey indicates that native Saudis need more participation and involvement in technology process in order to raise their technological know-how. As a result of this study, a common approach to technology transfer into Saudi Aramco and SABIC may be developed and applied by industry, per its requirements to address existing and prospective problems. At present Saudi Arabia has the capacity to absorb new technologies in its growing industrial sector. This is required to meet its desired objectives of becoming industrialised and self-sufficient in required technologies. The real test of effective technology transfer in this study is the need to build Saudi local technological capability supported by an effective learning strategy. The ultimate aim is to expand the scope of this study beyond the academic level towards the practical challenges of improving the efficiency and effectiveness of inward technology transfer for future Saudi industrial development.